ANALISIS DAYA TARIK MASYARAKAT TERHADAP LEMBAGA PENDIDIKAN DI MADRASAH ALIYAH NAHDLATUL ULAMA MARON PROBOLINGGO - Himmatul Aliyah; Kustiana Arisanti; Mahfudz Sulaiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the declining number of students at the Nahdlatul Ulama Senior High School (MA NU) in Maron over the past two years, despite the institution’s adequate facilities, strategic location, and affiliation with the large Nahdlatul Ulama organization. This situation indicates a gap between the institution’s internal potential and its perceived appeal in the eyes of the community. This study aims to describe public perceptions, identify factors influencing public interest and trust, and assess the quality of the madrasah as a basis for strategic recommendations for institutional development. The research method used is descriptive qualitative with a case study approach. Data were collected through non-participant observation, in-depth interviews with 10 informants (the madrasah principal, teachers, parents, alumni, and community leaders), and documentation. Data analysis was conducted through the stages of data collection, reduction, presentation, and drawing conclusions using triangulation validity techniques. The research results indicate that MA NU Maron is considered strong in fostering religious character through flagship programs such as the Qur’an memorization program and the cultivation of religious practices. However, this strength is hindered by the community’s negative perceptions regarding student discipline outside of school and the lack of variety in extracurricular activities. This study is important as a basis for evaluation to align administrative quality with the community’s practical expectations.